2015
DOI: 10.3389/fphys.2015.00081
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus species as biomarkers and agents that can promote various aspects of vaginal health

Abstract: The human body is colonized by a vast number of microorganisms collectively referred to as the human microbiota. One of the main microbiota body sites is the female genital tract, commonly dominated by Lactobacillus spp., in approximately 70% of women. Each individual species can constitute approximately 99% of the ribotypes observed in any individual woman. The most frequently isolated species are Lactobacillus crispatus, Lactobacillus gasseri, Lactobacillus jensenii and Lactobacillus iners. Residing at the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
348
2
19

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 395 publications
(380 citation statements)
references
References 178 publications
(268 reference statements)
11
348
2
19
Order By: Relevance
“…Strains of the Lactobacillus genus are widely acknowledged to be beneficial, and their properties have been reviewed extensively (20). Given their widespread association with a variety of different environments, including dairy, meat, vegetable, and grain-fermented foods and as commensals in the gastrointestinal tract, this genus has been widely consumed and also has been used in dietary supplements to promote general health and well-being (21)(22)(23). Recent human microbiome studies have identified Faecalibacterium prausnitzii as an organism with antiinflammatory properties and have reported it to be an indicator microbial population that was lowered in subjects with Crohn's disease and ulcerative colitis (10,24).…”
Section: Discussionmentioning
confidence: 99%
“…Strains of the Lactobacillus genus are widely acknowledged to be beneficial, and their properties have been reviewed extensively (20). Given their widespread association with a variety of different environments, including dairy, meat, vegetable, and grain-fermented foods and as commensals in the gastrointestinal tract, this genus has been widely consumed and also has been used in dietary supplements to promote general health and well-being (21)(22)(23). Recent human microbiome studies have identified Faecalibacterium prausnitzii as an organism with antiinflammatory properties and have reported it to be an indicator microbial population that was lowered in subjects with Crohn's disease and ulcerative colitis (10,24).…”
Section: Discussionmentioning
confidence: 99%
“…Among the Firmicutes, Streptococcus and Staphylococcus genera were detected, which could be associated with BV, and the genus Lactobacillus represented only about 17% of the BV vaginal bacterial biota, dominated by L. fermentum , L. casei , L. jonsonii , and L. salivarius species. It is noteworthy that vaginal Lactobacillus species can create a barrier against invasion by pathogens, since the products of their metabolism secreted in the cervicovaginal fluid play an important role in the inhibition of bacterial and viral infections [48]. In addition, the low vaginal pH (< 4.5) caused by the production of lactic acid by members of the genus Lactobacillus tends to suppress the growth of the pathogenic microorganisms that are mainly responsible for vaginal dysbiosis.…”
Section: Discussionmentioning
confidence: 99%
“…The dominance of Lactobacillus species such as L. iners, L. jensenii, L. gasseri, and L. crispatus in the vaginal region acts as a barrier for invasion of pathogenic bacteria and virus. Lactobacillus is an indicator of a healthy vaginal ecosystem, hence their rapid identification can prove helpful in diagnosing bacterial vaginosis [19][20][21].…”
Section: The Trouble With Lactobacillus Identificationmentioning
confidence: 99%
“…L. salivarius has acquired genes for bile salt hydrolase and the pentose phosphate pathway. Comparative genomics done through Differential Blast Analysis (DBA), used for identifying specific genome regions, also elucidated information on regions which were present in some and absent in another set of organisms [18,21,[43][44][45][46][47][48][49][50]. Lactobacillus helveticus DPC4571 show about 75 % homology with the genome of L. acidophilus NCFM [51].…”
Section: The Trouble With Lactobacillus Identificationmentioning
confidence: 99%